The Solovetsky monastery peasants at the eve of the 1764 secularization - Bogdanova Aleksandra; St. Tikhon’s University (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article deals with the peasants of the Solovetsky monastery at the eve of the secularization that took place in 1764. Description of the monastic estates and the feudal homage of the peasants is the subject of the article. The article uses archival documents stored in the Fund number 1201 («the Solovetsky monastery») and the Fund number 280 («Kollegia Jekonomii”) of the Russian state archive of ancient acts. The author asserts that the estates of the Solovetsky monastery could be divided into three groups according to their geographical location which determined the character of the basic obligations of the peasants. The estates located on the shore of the White sea or near it were allocated into the ﬁrst group. About 81 % of monastic peasants leaved there. They executed mixed duties: diﬀerent works in combination with monetary and food products servage. Working in the monastic salt mines was their main duty. They also had to deliver wood and send workers to the monastery. Money servage collected from these peasants was about the tenth part of the cash receipts of the monastic Treasury. The estates located on the banks of the Northern Dvina and Onega, the major Pomorian rivers (11 % of monastic peasants) composed the second group. Majority of peasants belonging to this group were “polovniki” whose duty was to work the monastic arable for half of the harvest. The monastic estates located in the Central districts of the country composed the third group (8 % of monastic peasants). The peasants belonging to this group had relatively weak connection with the monastery due to their geographical remoteness from the Solovetsky archipelago. Performing forced labor they provided bread for the Moscow monastic farmstead and Marchukova hermitage belonging to the monastery.